Gods of the Blood : The Pagan Revival and White Separatism - Gardell, Mattias (Book collections on Project MUSE., 2003)
An ethnographic study of the development of racist paganism in the United States during the 1990s, examining the economic, cultural, and political developments racist paganism reacts to or makes use of.